2022
DOI: 10.3389/fcvm.2022.803532
|View full text |Cite
|
Sign up to set email alerts
|

Valosin Containing Protein as a Specific Biomarker for Predicting the Development of Acute Coronary Syndrome and Its Complication

Abstract: BackgroundAcute coronary syndrome (ACS) consists of a range of acute myocardial ischemia-related manifestations. The adverse events of ACS are usually associated with ventricular dysfunction (VD), which could finally develop to heart failure. Currently, there is no satisfactory indicator that could specifically predict the development of ACS and its prognosis. Valosin-containing protein (VCP) has recently been proposed to protect against cardiac diseases. Hence, we aimed to assess whether VCP in serum can serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The remaining 52 (13.8%) proteins were specifically expressed, 14 of which were specific to the CAS group, and the remaining 38 proteins were specific to the control group ( Figure 1 B). In particular, the three ERS-related proteins (VCP, LMAN2, and CAPN-1), which we previously showed to associate with CAS-induced acute ischemia [ 16 , 17 ], were among the 52 specific proteins that supported the successful establishment of the CAS provocation model. To capture the greatest possible serum proteins, we used a rigorous criterion (with a fold change ≥2 and adjusted p -value < 0.05) for protein sorting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 52 (13.8%) proteins were specifically expressed, 14 of which were specific to the CAS group, and the remaining 38 proteins were specific to the control group ( Figure 1 B). In particular, the three ERS-related proteins (VCP, LMAN2, and CAPN-1), which we previously showed to associate with CAS-induced acute ischemia [ 16 , 17 ], were among the 52 specific proteins that supported the successful establishment of the CAS provocation model. To capture the greatest possible serum proteins, we used a rigorous criterion (with a fold change ≥2 and adjusted p -value < 0.05) for protein sorting.…”
Section: Resultsmentioning
confidence: 99%
“…Xanthine oxidoreductase activity, which plays a pivotal role in producing both uric acid and ROS, has also been reported to associate with CAS in clinical patients [ 15 ]. Endoreticulumn stress (ERS)-related secretory proteins such as valosin containing the protein (VCP), a vesicular integral membrane protein 36 (VIP36, also known as LMAN2), and Calpain-1 (CAPN-1) were considered as potential serological biomarkers for diagnosis of CAS-induced acute ischemia in our previous studies [ 16 , 17 ]. These studies led to transitions from a standard yet risky diagnostic strategy to a non-invasive biochemical diagnostic detection.…”
Section: Introductionmentioning
confidence: 99%
“…There are candidates from the shortlist that have been proposed as potential biomarkers for different types of vascular complications. E.g., serum VCP level was higher in patients with acute coronary syndrome when compared to healthy control or chronic coronary syndrome [ 38 ]. Serum VCP level was increased in myocardial ischemia-induced sudden cardiac deaths when compared to matched control patients who died from non-cardiac causes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that there is a direct correlation between CA II activity and diabetes, in the sense that diabetic patients have higher values of this isoenzyme, while CA I isoenzyme, known for its implications in vasoconstriction and vasodilation, has increased activity in all patients with myocardial infarction, regardless of their diabetic status [ 30 , 31 , 32 ]. The high values of CA II are also correlated with the high values of cardiac markers, meaning that the enzyme can also be an indicator of the state of damage to the heart tissue [ 33 ]. A long-term case follow-up study is needed to investigate the incidence of diabetes and cardiovascular complications of the disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%